Effect of Phosphorus Fertilizer on Growth, Phosphorus Uptake, Seed Yield, Yield Components, and Phosphorus Use Efficiency of Oilseed Flax. (1st May 2016) - Xie, Yaping; Niu, Xiaoxia; Niu, Junyi
Abstract : Improving the seed yield of oilseed flax ( Linum usitatissimum L.) is an important issue to meet the growing demand for this crop. This study was conducted to determine whether various aspects of oilseed flax growth could be manipulated through P under the arid and semiarid conditions in China. The effects of P on oilseed flax phenological stages, seed yield, yield components, biomass growth rate (BGR), and phosphorus uptake rate (PUR) were investigated at Zhangjiakou, China. The Baxuan 3 flax cultivar was grown on a P deficient soil, to which four rates of P fertilizer were applied (0, 15, 30, and 45 kg P ha −1 ). Our results indicated that the application of P increased the number of capsules per plant, seed weight, seed yield, and the oil yield by 20, 19, 44, and 56%, respectively, compared with the 0P control treatment. At 30 kg P ha −1, the apparent phosphorus recovery efficiency (APE) was higher than those at 45 kg P ha −1 . However, at 15 kg P ha −1, agronomic efficiency (AE) was higher than those at 30 and 45 kg P ha −1 . The seed‐filling period, the growth rates (biomass, economic, and seed) and the P uptake rates (biomass, economic, and seed) were significantly improved by P application. A linear positive relationship was found between seed yield and number of capsules per plant, seed weight, growth rates, and P uptake rates. The results suggest the addition of P fertilizer enhanced growth and P uptake, and increased seed yield of oilseed flax. Core Ideas The effect of P application on key biomass growth rate and P uptake rate indices. Phosphorus increase number of capsules per plant, mean seed weight, seed‐filling period and days to maturity. Phosphorus promotes the growth of oilseed flax, P uptake, and increase the seed yield and oil yield.